Kajian Systematic Literature Review: Implementasi Pendidikan Karakter Berbasis Budaya Lokal di Sekolah Dasar - Rizki Yustikasari; Ajeng Carolina Samrodi; Wasino; Argitha Aricindy (Advances In Education Journal, 2026)
Character education is an important aspect of learning in elementary schools, especially in shaping students’ personalities from an early age. One effective approach is integrating local cultural values into the learning process. This study aims to examine the forms of implementation of local culture-based character education, the values developed, and its effectiveness based on previous studies. This research uses the Systematic Literature Review (SLR) method following the PRISMA guidelines. Data were collected from Google Scholar, SINTA, and Garuda, with 100 articles identified at the initial stage and 25 articles selected after the screening process based on inclusion criteria. The results show that the implementation of character education based on local culture is carried out through classroom learning, school culture and habituation, extracurricular activities, and the development of learning media and teaching materials. The character values developed include religiosity, discipline, responsibility, cooperation, tolerance, and social awareness. Overall, this approach is proven to be effective in improving students’ knowledge, attitudes, and behavior. However, there are still several challenges, such as limited facilities, teacher competence, and students’ awareness. Therefore, support from various stakeholders is needed to optimize its implementation. This study is expected to serve as a reference for developing local culture-based character education in elementary schools.